2020
DOI: 10.1101/2020.06.10.144931
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tubulin acetylation increases cytoskeletal stiffness to regulate mechanotransduction in striated muscle

Abstract: Microtubules tune cytoskeletal stiffness to regulate the mechanics and mechanotransduction of striated muscle. While recent evidence suggests that microtubules enriched in detyrosinated α-tubulin are responsible for these effects in healthy muscle, and for their excess in disease, the possible contribution from several other α-tubulin modifications has not been investigated. Here we used genetic or pharmacologic strategies in isolated cardiomyocytes or skeletal myofibers to increase the level of acetylated α -… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…51 Dystrophin functions as an intermediary between membrane and cytoskeleton biology, and it is known that the lack of dystrophin in DMD results in cytoskeletal disruptions, such as microtubule dysregulation and increased cytoskeletal stiffness, 71 as well as abnormalities in plasma membrane structure and function resulting in calcium overload. 72,73 A stiff cytoskeleton may result in increased cellular viscoelastic resistance leading to systolic and diastolic cardiac dysfunction, 74 possibly by directly impairing the contraction cycle. Similarly, elevated intracellular calcium due to sarcolemmal damage in DMD results in cardiomyocyte hypercontraction, and thus decreased sarcomere lengths as well as low contractility and slow relaxation.…”
Section: Discussionmentioning
confidence: 99%
“…51 Dystrophin functions as an intermediary between membrane and cytoskeleton biology, and it is known that the lack of dystrophin in DMD results in cytoskeletal disruptions, such as microtubule dysregulation and increased cytoskeletal stiffness, 71 as well as abnormalities in plasma membrane structure and function resulting in calcium overload. 72,73 A stiff cytoskeleton may result in increased cellular viscoelastic resistance leading to systolic and diastolic cardiac dysfunction, 74 possibly by directly impairing the contraction cycle. Similarly, elevated intracellular calcium due to sarcolemmal damage in DMD results in cardiomyocyte hypercontraction, and thus decreased sarcomere lengths as well as low contractility and slow relaxation.…”
Section: Discussionmentioning
confidence: 99%
“…The periodic, lateral reinforcement of microtubules increases their stability, leading to longer-lived microtubules and providing a dynamic cross-link with the sarcomere, increasing the viscoelastic resistance to myocyte motion and the ability of microtubules to transduce mechanical stress. Increased microtubule lifetimes also promote microtubule acetylation, which itself increases the ability of microtubules to withstand mechanical stress 35 and increases myocyte viscoelasticity 36 . In the setting of heart disease, the increased abundance of both desmin intermediate filaments and detyrosinated microtubules thus promotes a feed-forward substrate for enhanced mechanotransduction and myocardial stiffening.…”
Section: Discussionmentioning
confidence: 99%
“…4i). Increased acetylation due to the loss of MeCP2 may play a role in muscle function as hyperacetylation has been shown to increase stiffness and resistance in striatal muscles in vitro 54 . We continued to evaluate the possible impact of tubulin acetylation by examining the colon, a biomechanically-active organ that is often distended in Rett patients and may play a major role in digestive tract disruption that is a major complaint of these patients clinically 53 .…”
Section: Oral Vorinostat Exhibits Broad Efficacy In Rett Mice Even Af...mentioning
confidence: 99%
“…In addition, we explored the potential link of tubulin acetylation with muscle function and found that vorinostat treatment can rescue the disrupted α-tubulin acetylation observed in femoral muscle sections ( 4 ). Increased acetylation due to the loss of MeCP2 may play a role in muscle function as hyperacetylation has been shown to increase stiffness and resistance in striatal muscles in vitro 54 .…”
Section: Oral Vorinostat Exhibits Broad Efficacy In Rett Mice Even Af...mentioning
confidence: 99%